Efficient estimation of non parametric simultaneous equations models. Issue 7 (3rd April 2017) - Tu, Y.
ABSTRACT: This paper defines a new procedure to efficiently estimate non parametric simultaneous equations models. The proposed estimation procedure exploits the additive structure and achieves oracle efficiency without the knowledge of unobserved error terms. Furthermore, simulation results show that our new estimator outperforms the existing estimator in terms of mean squared error.